The current status and influencing factors of core competencies among China’s internet-based “sharing nurses” based on social-ecological system theory: a multicenter cross-sectional study - Yudong, Wang; Zhaowei, Xing; Linlin, Jiao; Yishu, Zhang; Jianghua, Wu; Linlin, Yang; Chunling, Yang (Frontiers in Medicine, 2025)
AimsThis study aims to investigate the current status of core competencies and emergency response competencies among Chinese sharing nurses, examine the correlation between core competencies and emergency response competencies, and identify the factors influencing the core competencies of these nurses.MethodsThis multicenter cross-sectional study was conducted in July 2025 at 6 hospitals in 6 cities in Shandong Province, with 1,011 nurses participating in the study. Data were collected using the following tools: (1) a socio-demographic questionnaire, (2) the Core Competency Assessment Tool for “sharing nurses,” and (3) evaluation index system for emergency response competencies of “Internet+” nurses. SPSS 26.0 was used to analyze the data, Spearman correlation analysis was used to evaluate the correlation between the core competencies of “sharing nurses” and emergency response competencies, and linear regression was used to explore the factors influencing the core competencies of these nurses.ResultsAmong the 1,011 participating nurses, 41.05% had delivered more than one Internet-Based nursing service. A significant positive correlation was observed between the core competencies of “sharing nurses” and their emergency response competency scores (r = 0.852; p < 0.001). The level of “sharing nurses” core competencies was influenced by the following factors: hospital level, hospital leadership support, team therapeutic support, family support, nurse personality, subjective willingness, training experience, and emergency response competencies.ConclusionChinese “sharing nurses” demonstrated a high level of core competencies and emergency response abilities, and the two are closely related. Based on these findings, healthcare institutions should actively provide standardized training in accordance with national policies, with an emphasis on enhancing nurses’ subjective willingness to become “sharing nurses” and promoting the actual delivery of nursing services. Supported by hospital-based therapeutic teams, these efforts will help safeguard the quality of life and safety of home-based patients, while also providing a foundation for refining the “Internet+ nursing service” model and optimizing the allocation of primary healthcare human resources.